Nontraditional systems in aging research: an update - Mikuła-Pietrasik, Justyna; Pakuła, Martyna; Markowska, Małgorzata; Uruski, Paweł; Szczepaniak-Chicheł, Ludwina; Tykarski, Andrzej; Książek, Krzysztof (Cellular and Molecular Life Sciences, 2020)
Abstract Research on the evolutionary and mechanistic aspects of aging and longevity has a reductionist nature, as the majority of knowledge originates from experiments on a relatively small number of systems and species. Good examples are the studies on the cellular, molecular, and genetic attributes of aging (senescence) that are primarily based on a narrow group of somatic cells, especially fibroblasts. Research on aging and/or longevity at the organismal level is dominated, in turn, by experiments on Drosophila melanogaster , worms ( Caenorhabditis elegans ), yeast ( Saccharomyces cerevisiae ), and higher organisms such as mice and humans. Other systems of aging, though numerous, constitute the minority. In this review, we collected and discussed a plethora of up-to-date findings about studies of aging, longevity, and sometimes even immortality in several valuable but less frequently used systems, including bacteria ( Caulobacter crescentus , Escherichia coli ), invertebrates ( Turritopsis dohrnii, Hydra sp., Arctica islandica ), fishes ( Nothobranchius sp., Greenland shark), reptiles (giant tortoise), mammals (blind mole rats, naked mole rats, bats, elephants, killer whale), and even 3D organoids, to prove that they offer biogerontologists as much as the more conventional tools. At the same time, the diversified knowledge gained owing to research on those species may help to reconsider aging from a broader perspective, which should translate into a better understanding of this tremendously complex and clearly system-specific phenomenon.